Experiment of Contextual Teaching and Learning (CTL) and Problem-Based Learning (PBL) Models on Learning Motivation Akidah Akhlak - Latifatus Sa’diyah; Choirudin Choirudin; Eka Fitria Ningsih (Assyfa Journal of Multidisciplinary Education, 2026)
Experiment of Contextual Teaching and Learning (CTL) and Problem-Based Learning (PBL) Models on Learning Motivation Akidah Akhlak